Case series of cutaneous diphtheria in children - Dr Aishatu Jibril; Dr Salma Suwaid; Dr Hauwa Makarfi; Prof Hafsah Ahmad (International Journal of Infectious Diseases)
Background: Cutaneous diphtheria is caused by infection with Corynebacterium diphtheriae. Transmission from cutaneous lesions can cause both respiratory and cutaneous disease in susceptible contacts.Literature on cutaneous diphtheria report it to be rare post vaccination era due to increased vaccine coverage, but cutaneous diphtheria as an re emerging disease is still common in the tropics and maybe confused with other tropical dermatological disease considering the non- specific pattern of presentation of cutaneous diphtheria.Considering the role of cutaneous diphtheria during outbreaks, a high index of suspicious is required not to miss the diagnosis.It is an important reservoir for ongoing transmission within a susceptible population, and likely to be diagnosed less quickly than respiratory infection because the clinical appearance is nonspecific, and other pathogens often co infect the lesions. Case report: At the beginning of the outbreak, 3 cases of cutaneous diphtheria was reported, all had pseudomembrane with zero with vaccination statusNone had a preexisting skin, only one of the patient survived.Case 1An 8 year old boy who presented with history of cough, fever, inability to swallow, generalised body rash, bleeding from the mouth and nose with abnormal breathing and reduced urine output for 1 week.Had lost 3 siblings to similar illness 2 weeks prior to presentation On examination, he was in severe respiratory distress, generalised bullous skin lesions with areas of desquamation, bull neck, hallitosis, bleeding from the mouth and throat, severely pale. Pulse was small volume and threadyA diagnosis of haemorrhagic diphtheria with cutaneous manifestation in shock. He died within an 1hr of admission.Case 2A 17 year old girl presented with sore throat, fever and cough for 4 days 3 days into admission she complained of vulval swelling and dysuria. Genitourinary examination reveals an edematous vulva with an adherent greyish white membrane. Serology screening and vaginal swabs were both negative, however, histocytology report was highly suggestive of diphtheria. She was discharge after spending 12 days on admission to continue with Sitz bath with diluted hydrogen peroxide.Case 3A case of an infant with both throat and vaginal pseudomembrane, she died from sudden cardiac arrest after 6 days on admission. Discussion: The report highlighted case series of cutaneous diphtheria in children with different presentation of haemorrhagic and ulcer.Cutaneous diphtheria may have played a role in the outbreak as all the patients were from the epicenter of the outbreak. Conclusion: Cutaneous diphtheria should be considered as a differentials of a non healing and painful skin ulcers with greyish membrane especially in a child with poor vaccination history..